Influence of mountain orientation on precipitation isotopes in the westerly belt of Eurasia - Chen, Longhu; Zhu, Guofeng; Wang, Qin Qin; Ye, Linlin; Lin, Xinrui; Lu, Siyu; Jiao, Yinying; Li, Rui; Meng, Gaojia; Wang, Yuhao; Yang, Jiangwei; Jia, Chen (Global and planetary change, 2024)
Mountains have a significant impact on the transport path of water vapour and local meteorological variations. Therefore, understanding the influence mechanism of mountains on stable isotopes of precipitation is essential. In this study, we analyzed the precipitation stable isotope data within the Westerlies in the Eurasian continent. The results indicate the following: (1) East-west-oriented mountain ranges and plains play a “channelling role” in facilitating the inland penetration of westerly moisture, with this effect being more pronounced in the northern part of the Alps. Conversely, north-south-oriented mountain ranges and plateaus act as a “barrier” to westerly moisture. (2) Mountains influence stable isotopes of precipitation primarily by altering the water vapour movement paths and regulating local meteorological factors. (3) The “altitude effect” is the most common mechanism through which mountains affect local meteorological elements reflected in stable isotopes of precipitation. Furthermore, we anticipate that with global climate warming, the interaction and feedback between mountains and climate will become even more complex. This aspect deserves consideration in future research. •Stable isotopes reveal how mountains impact large-scale meteorological elements.•Mountains change water vapour paths, affecting stable isotopes and local weather patterns.•East-west mountains channel westerly moisture, while north-south ranges and plateaus block it.